Escalation of Online Zakat in New Normal - Maulida Dwi Agustiningsih; Ravika Mutiara Savitrah; Putri Catur Ayu Lestari (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
Now adays, the world is still struggling in dealing with Covid-19 and all the effects it causes. This condition has many impacts, including on the socio-economic sector and can be overcome by increasing zakat income. Given the extremely dangerous nature of the transmission of the corona virus, WHO recommends the use of digital money. This also applies to the payment of zakat through e-zakat (online payment of zakat). This study aims to determine the factors that influence Muzakki's decision to pay zakat online.This study uses a younger generation as a sample because of its role as the largest internet users who are able to easily learn the latest technology. This research contributes to providing new insights regarding the factors that influence consumers in using e-zakat. This research has implications for amil zakat institutions to innovate through e-zakat services and improve their services so that more consumers can serve so that the number of users will increase. Research instrument used to obtain data was a likert scale questionnaire. The research model used is the Structural Equation Model (SEM) and analyzed using PLS to test the measurement model and the structural model simultaneously. Based on the results of hypothesis testing, e-wom and religiosity have a positive effect on the decision to pay zakat. Meanwhile, the intention variable proved insignificant in moderating the relationship between e-wom and religiosity towards the decision to pay zakat online.Â Keywords: e-wom, religiosity, intention, decision